Kajian studi awal dan validasi lembar kerja siswa tema peran energi bagi makhluk hidup mengintegrasikan literasi saintifik untuk siswa SMP kelas VII - fuzia anggraini; Renol Afrizon; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2019)
ABSTRACTThe 21st century requires graduates of education to have good and holistic competence. For this reason, the Indonesian government has implemented the 2013 curriculum so that graduates of education are able to compete in the 21st century. The teaching science in the 2013 curriculum should be implemented in an integrated form and be integrated the literacy skills. The results of the initial study that have been conducted indicate that integrated Science teaching cant be implemented well and literacy skills of students were still weak. The solution to this problem is to develop an integrated Science student worksheet with scientific literacy. The purpose of this research was to describe the results of the initial study and determine the value of the validity of the integrated Science student worksheet on the theme of the role of energy for living things with scientific literacy. This type of research was research and development (R & D). The object of the research was the integrated Science student worksheet on theme of the role of energy for living things with scientific literacy. The instruments for collecting data consist of observation sheet, document analysis, interview sheet, and questionnaire sheet for validity test. The components of validity assessment include the content feasibility, presentation, language, and graphics. The data analysis technique was descriptive statistics. From the data analysis, the result of this research can be stated in two parts. First, the integration of science learning material in the teaching process and in student worksheet was insufficient and low category respectively. Literacy integration in science teaching was still limited in the form of reading skills. Second, the average value of validity from integrated science student worksheet on the theme the role of energy for living things with scientific literacy is 84 and this average value can be classified into a very good category.